2017
DOI: 10.1111/acem.13227
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Physical Examination, Ankle‐Brachial Index, and Ultrasonography in the Diagnosis of Arterial Injury in Patients With Penetrating Extremity Trauma: A Systematic Review and Meta‐analysis

Abstract: In PET patients, positive US may obviate CTA. In patients with a normal examination (no hard or soft signs) and a normal ABI, arterial injury can be ruled out. However, a normal ABI or negative US cannot independently exclude arterial injury. Due to high study heterogeneity, we cannot make recommendations when hard signs are present or absent or when ABI is abnormal. In these situations, one should use clinical judgment to determine the need for further observation, CTA or catheter angiography, or surgical exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…Multiple studies have found that IEI reduces the need for CTA in evaluating for vascular injury. 8 13 Regardless, this study supports the use of other examination findings in settings in which IEI cannot be performed. This includes pulse examination, although that itself may be limited and varied in the emergency department and trauma setting.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Multiple studies have found that IEI reduces the need for CTA in evaluating for vascular injury. 8 13 Regardless, this study supports the use of other examination findings in settings in which IEI cannot be performed. This includes pulse examination, although that itself may be limited and varied in the emergency department and trauma setting.…”
Section: Discussionsupporting
confidence: 68%
“…These include careful physical examination, calculation of an injured extremity index (IEI), ultrasound, and CT angiography (CTA). 8 The IEI is a useful index analogous to the ankle brachial index; it describes the ratio of systolic occlusion pressure between injured and uninjured extremities. There are a number of published test characteristics of these methods from the past decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by DeSouza et al,8 however, appears to support ultrasound as a viable and accurate option. The authors examined a large database of studies that included ED patients with penetrating extremity injuries.…”
Section: Discussionmentioning
confidence: 97%
“…The consultant was satisfied with the ultrasound images and felt in this case the injury could be safely observed without advanced imaging. This management has been previously described as satisfactory when no hard signs of limb-threatening vascular injury are present [ 14 ].…”
Section: Case Reportmentioning
confidence: 99%